EVALUASI PENERAPAN PLN LIFE RULES PADA PROYEK X PT PLN (PERSERO) UPP JBB 3 TAHUN 2022 - Namira Adha (2023)
PLN Life Rules is a guideline of Occupational Health and Safety (OHS) behavior established by the company to prevent occupational accidents. In its implementation, several gaps in its management elements have been discovered. The purpose of this study was to evaluate the implementation of PLN Life Rules at Project X PT PLN (Persero) UPP JBB 3 in 2022. This study used a descriptive qualitative study design. A total of 5 workers, including PLN and contractor safety officer, OHS executive officer, OHS junior engineer and one of the project X workers, were recruited as informants by using a purposive sampling technique. Data collection was carried out by in-depth interview, observation and documents review. The results showed that the human resources of working at height and stop working authority have not been sufficiently fulfilled; the implementation budget was not presented in details; the facilities, infrastructure and SOP required for implementing the PLN Life Rules were still incomplete. It is suggested to the management of Project X and PT PLN (Persero) UPP JBB 3 to recruit additional OHS human resources and building their competences, make a specific budgeting, provide PPE storage, work area restriction, complete procedures and socialize it.